Античне поселення Новопокровка-І у Південно-Східному Криму - Гаврилов, О.В. (Археологія, 1999)
Публікуються результати дослідження і дається повний аналіз археологічних матеріалів поселення античного часу Новопокровка-І, визначається місце пам'ятки як серед подібних на сільській окрузі Феодосії, так і Європейського Боспору. Несмотря на давнюю известность, неукрепленные поселения античного времени в округе Феодосии изучены слабо. Поэтому археологическое исследование каждого нового памятника значительно расширяет источниковедческую базу для изучения истории населения Юго-Восточного Крыма в V—III вв. до н. э. Поселение у села Новопокровка Кировского района располагалось на склоне степной лощины и состояло из 9 золистых пятен, обозначавших места жилищно-хозяйственных комплексов. Судя по местонахождению пятен, жилищно-хозяйственные комплексы располагались на местности относительно компактно, но бессистемно. Раскопками было раскрыто наземное каменно-сырцовое, прямоугольное в плане, многокамерное жилище общей площадью более 104 м2. Оно имело земляные полы и камышовую или покрытую глиной крышу. Исследованы также внутренние и внешние очаги; зерновые, хозяйственные, столбовые ямы, глинобитная площадка — ток, колодец, свалка амфорного боя. Вещественный материал разнообразен и представлен фрагментами амфор, гончарной и лепной кухонной и столовой посуды; изделиями из железа, бронзы, глины, камня, которые характеризуют различные стороны хозяйственной деятельности, быта, духовной культуры проживавшего здесь населения. Проведены палеоботанические, палеозоологические, минералопетрографические анализы полученного материала. Результаты исследований показывают, что поселение возникло в начале V и прекратило существование в конце первой трети III в. до н. э. Население состояло преимущественно из варваров: кизил-кобинцев (тавров) и скифов, основой их хозяйственной деятельности было земледелие. Despite of long-lasting popularity the unfortificated sites of antique times in the Theodosia neighborhood are investigated poorly. Therefore, the archaeological research of each new monument expands the source base for the study of the history of the South-East Crimea population in the V–III centuries В. C. The site near the village of Novopokrovka in Kirov region is placed on a slope steppe hollow and consists of 9 ash stains, designating places of dwelling-economic complexes. Judging by the site's location, the dwelling-economic complexes were placed rather compactly but irregularly. By the excavations, the ground stone-clay, rectangular in plan, multychamber building was found. It occupied a common area of more than 104 m2. The building had ground floors and a reed roof covered with clay. The internal and external seats of the fire, grain, economic, pole holes, clay platform-current, will, and amphorae sherds heap were investigated. The material is diverse and is submitted by amphoras, fine and ware vessel fragments, by artifacts made of iron, bronze, clay, and stone which characterize the various parties of economic activity, mode of life, and spiritual culture of the living population. Paleobotanical, paleozoological, and mineralogical analyses of the received material are made. Results of research show that the site arose by the beginning of the 5th century В. C. and stopped existence at the end of the first third of the 3rd century В. C. The population consisted mainly of the barbarians: the Taurians and the Scythians, the basis of its economic activity was agriculture.